Myoepithelial carcinoma treatment in children: A report from the TREP project. Issue 4 (18th October 2013) - Bisogno, Gianni; Tagarelli, Arianna; Schiavetti, Amalia; Scarzello, Giovanni; Ferrari, Andrea; Cecchetto, Giovanni; Alaggio, Rita
Abstract Background Myoepithelial carcinoma (MC) of soft tissues is an aggressive tumor that rarely affects children, for whom no established treatment protocols exist. As part of the TREP (Tumori Rari in Età Pediatrica) project – an Italian network dedicated to children and adolescents with very rare tumors – we present a series of patients with MC, who were treated homogeneously and achieved a satisfactory outcome. Procedure From 2005 to 2012, seven patients (age 0.5–9.2 years) with a diagnosis of MC were registered in the TREP study. After one patient treated with ifosfamide, cisplatin, and etoposide showed tumor shrinkage and experienced long‐term disease remission, all subsequent patients were treated with the same chemotherapy regimen. All patients also received radiotherapy. Results Initial surgical management involved a biopsy in three cases and tumor resection in 4. Response to initial chemotherapy was evaluable in four patients: two had a partial remission, one a minor response and one stable disease. Four patients received external‐beam radiotherapy and three had brachytherapy. Overall, six patients are alive in first complete remission with a median follow‐up of 2.5 years (0.9–5.1 years). Conclusions Though our experience is limited to a small number of patients, our treatment strategy for patients with MC is appears clinically useful and demonstrates how cooperation within the TREP project has enabled enough data to be collected to propose treatment recommendations for pediatric patients with this very rare tumor. Pediatr Blood Cancer 2014;61:643–646. © 2013 Wiley Periodicals, Inc.